Characterizing plasma focus devices - Role of the static inductance - Instability phase fitted by anomalous resistances - Lee, S.; Saw, S. H.; Abdou, A. E; Torreblanca, H. (Springer US, 2011)
Plasma focus devices with low static inductance L 0 (type T1) are found to be well modeled by the 5-phase Lee code; whereas those with high L 0 (type T2) are found to have an extended dip ED beyond the regular dip RD modeled by the code. Differentiating factors based on inductance and inductive energy ratios are found and the physics explained. To model type T2’s, anomalous resistance terms are proposed extending the model to 6 phases. These anomalous resistance terms represent the plasma instabilities that occur during and after the pinch phase. The fitted terms are experimental results derived from the measured current waveform. An example is tested to validate the method.